2015
DOI: 10.1016/j.jnc.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Debunking the myth that a legal trade will solve the rhino horn crisis: A system dynamics model for market demand

Abstract: There is considerable debate in the literature over whether or not to legalise the trade in rhino horns. Here a system dynamics model is developed that considers five components: rhino abundance, rhino demand, a price model, an income model and a supply model. The results indicate that income elasticities are much greater than previously observed, while demand is relatively insensitive to price. At the same time, legalising the trade without income modification policies did not prevent extinction. The theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…This finding implies that there is an incentive for wildlife authorities to maximise short-term revenues at the expense of the long-term sustainability of the abalone population. A similar effect was observed by Crookes and Blignaut 24 in their model of the trade in rhino horn. They found that, although a legalisation of the trade increased the profitability of game farms significantly compared with a no-trade scenario, profits were higher under a policy outcome that resulted in the local extinction of the rhino population compared with profits under a sustainable supply of rhino.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding implies that there is an incentive for wildlife authorities to maximise short-term revenues at the expense of the long-term sustainability of the abalone population. A similar effect was observed by Crookes and Blignaut 24 in their model of the trade in rhino horn. They found that, although a legalisation of the trade increased the profitability of game farms significantly compared with a no-trade scenario, profits were higher under a policy outcome that resulted in the local extinction of the rhino population compared with profits under a sustainable supply of rhino.…”
Section: Discussionsupporting
confidence: 84%
“…In the case of rhinos and abalone, a legalised trade must be accompanied by secondary policies, for the sustainability of the resource to be achieved. For rhinos, this secondary policy is consumer behaviour modification that reduces demand, 24 whereas for abalone, it is improving the probability of detection prior to an offence. Under costly enforcement, the market does not provide the incentives to adopt these secondary policies, because profits are higher without them.…”
Section: Discussionmentioning
confidence: 99%
“…The income elasticity of rhino horn demand also needs to be better understood. Crookes & Blignaut (2015) recently confirmed Milner- Gulland's (1993) finding that rhino horn is a luxury good, which suggests that demand for rhino horn is income elastic 3 . However, there is insufficient evidence on the elasticity of the demand for rhino horn.…”
Section: Revenue From Poachingmentioning
confidence: 70%
“…Despite these high prices and the fact that rhino horn is contraband, the Asian market for rhino horn persists, suggesting that 1 Ceteris paribus is a Latin phrase that is used by economists to denote 'all other things being equal' or 'other things held constant'. the demand for horn is price inelastic or insensitive to price changes 2 ('t Sas-Rolfes 2012; see also Crookes & Blignaut 2015).…”
Section: Revenue From Poachingmentioning
confidence: 99%
See 1 more Smart Citation